Habitat suitability and projecting distribution shifts of Himalayan Monal (Lophophorus impejanus) habitats across changing landscapes of the Indian Himalayan region - Rajeev Lochan; Dinesh Kumar Sharma; Anand Kumar (Scientific Reports)
Abstract The accelerated pace of climate change is altering the distribution of numerous taxa, including Himalayan Galliformes, which are highly sensitive to environmental changes due to their specialized habitat preferences. The Himalayan Monal (Lophophorus impejanus), a flagship species, relies on specific vegetation, microclimates, and elevations in IHR. This study uses Species Distribution Modeling (SDM) using MaxEnt to evaluate current (1980–2010) and future habitat suitability using the CMIP6 mpi-esm1-2 h model across three socioeconomic pathways. Nineteen bioclimatic variables were analyzed, and to eliminate highly correlated variables, autocorrelation thresholds (r > 0.7) were used in ArcGIS. Model performance and accuracy were assessed with AUC and TSS values. We used a total of 5,122 occurrence points and 10-fold cross-validation. Predictions indicate habitat shifts, with SSP126 showing a 14.60% loss of stable areas (177,549.61 km2) by mid-century, while SSP585 predicts a 3.79% gain (45,258.23 km2). Precipitation of the coldest quarter emerged as a key variable, with optimal habitat suitability (HSI 0.7-0.98) at 1,800 − 10,000 kgm2/month precipitation levels. Extreme precipitation (> 10,000 kgm2/month) reduced HSI to 0.5–0.6. These findings emphasize the dual challenges of habitat loss and expansion opportunities, underscoring the need for conservation strategies to protect this species amidst the shifting Himalayan climate.